The Stratigraphic Log drawing using GeoMS Software, Case Study: Semilir Formation, Ngoro-oro Area, Bantul, Yogyakarta - Rahmad, Basuki; Nugroho, Muchamad Ocky Bayu; Rahardjo, Sugeng; Rachman, Muhamad Gazali; Al Hakam, Rahmat Aziz; Al Fatah, Muhamad Imam (RSF Conference Series: Engineering and Technology, 2022)
The stratigraphic log is the standard method used to display the vertical succession of rock layers from oldest to youngest. Stratigraphic sections can be constructed based on field data and drilling data. There are two stages when using field data to create a stratigraphic cross-section. The first stage is data correction and the second stage is stratigraphic log depiction. Data correction is done manually using trigonometric empirical formulas and the drawing was done using graphic software such as CorelDraw. These stages of course needs more time and effort. GeoMS is a simple software that was designed and built for drawing sedimentary and stratigraphic logs. The software focus on field data processing, although it can use core data or well logs, so the user can choose the data source correctly. The aim of using GeoMS is to simplify and speed up work with precise and detailed results so that it is more efficient and accurate. The research is explain the new technique of stratigraphic log drawing simpler with any type of data. Beside that, the result is still have an accuracy and detail as good as manually drawn. The stratigraphic log of Semilir Formation in the Ngoro-oro area was successfully drawn using GeoMS. The results of the stratigraphic logs are more detailed and precise due to computational work. However, additional columns such as lithological composition, fossil, facies, noted, photos, etc have been another advantages .GeoMS was proven to provide maximum results in a faster time.